Gender representations in the Polish public space – an attempt to capture the dynamics of the discourse - Grochalska, Monika (Kultura-Społeczeństwo-Edukacja, 2020)
Before 2013, the term ‘gender’ as used to define male and female social roles had appeared relatively rarely in the public sphere. However, it had not been completely unknown. Whenever this term did occur in utterances of public figures, it was mostly in reference to equality policies (gender policy) and the idea of gender mainstreaming in EU projects. It was commonly associated with feminism and has in this form entered the social consciousness, including the minds of major public figures, especially those with highest state positions. The situation changed radically in 2013. The term ‘gender’ started to be connected with ‘gender ideology’, a term coined by people associated with the Catholic Church. This article presents the ways in which the issues related to the broadly meant gender are presented on the right and left sides of the political scene. This analysis is based on selected interviews and other utterances of famous politicians as well as the articles in popular weekly magazines published in 2011–2015. This paper covers both kinds of utterances – those in line with the rules of political correctness and the examples of hate speech. All examples are provided to highlight the mechanisms of discrimination hidden in the language of politics.